Customer Churn in the Private Banking Industry in Iran - Mirza Hassan Hosseini; Mohammd Reza Hamidizadeh; Ali Akbar Jokar; Mahdi Rezaei (مطالعات مدیریت راهبردی, 2016)
The present study aimed to explore the Factors Affecting valuable customer churn in the private banking industry was conducted with a focus on community specialist physicians. The population of the study subjects comprised of 59 specialist physicians in metropolitan of Tehran. To collect data, the two sets of open and close questionnaires were used and the research methodology was a combination of three methods DEMATEL, ANP, and VIKOR that are part of multi-criteria decision methods. In the end, the results are interesting and functional specialist physicians in turn causes a branch banking (or bank) was given which can be programmed for micro and macro banks in the field of marketing to attract and retain a certain stratum of society. This study is a survey-heuristic approach has been carried out with the purpose of application.